A new species of Aquanirmus Clay and Meinertzhagen, 1939 (Phthiraptera, Philopteridae) parasitic on Rollandia rolland chilensis (Lesson, 1828) (Aves, Podicipitidae), with remarks on the external chorionic morphology of the egg - Castro, Dolores del Carmen (2000)
The authors describe the new species Aquanirmus rollandii n. sp. based on specimens collected on Rollandia rolland chilensis (Lesson, 1828) from Arhentina, which belongs to the "bahli-group" (sensu Edwards, 1965). Characters of the male, female and of the external architecture of the eggs have been used for the descriptions.